Association between Bone Mineral Density and Bone Turnover Markers in Breast Cancer Patients and Bone-Only Metastasis - Kundaktepe, Berrin Papila; Sozer, Volkan; Kundaktepe, Fatih Orkun; Durmus, Sinem; Papila, Cigdem; Uzun, Hafize; Simsek, Gonul; Gelisgen, Remise (MDPI, 2021)
Background and Objectives: The aim of this study was to determine the influence of bone turnover markers, namely the N-terminal cross-linking telopeptide (NTx) and alpha C-terminal cross-linking telopeptide of type I collagen (alpha-CTx), in detecting bone metastasis (bone-only) in breast cancer (BC) patients, as well as to determine whether this effect is related to changes in bone mineral density (BMD). Materials and Methods: The participants in this study comprised 30 postmenopausal BC patients with bone metastases (age range: 59.56 +/- 9.02), 20 postmenopausal BC patients without bone metastases (age range: 55.30 +/- 11.55), and 20 healthy postmenopausal female controls (age range: 55.55 +/- 5.85). Bone turnover markers (serum NTx and urine alpha-CTx) were measured using the ELISA method. A densitometer using dual-energy X-ray absorptiometry (DEXA) was used to analyze the BMD, and tumor markers were measured using the chemiluminescent immunometric assay. Results: The corresponding levels of serum NTx (p = 0.004), parathyroid hormone (PTH) (p = 0.001), and urine alpha-CTx (p < 0.001) of BC patients were found to be higher than the standard levels. After the BC patients were divided into subgroups on the basis of the presence of metastasis, the urine alpha-CTx levels (p = 0.001) were seen to be at critically high levels in those patients suffering from BC with metastasis. Though the BMD values in the lumbar spine (p < 0.001) and femoral neck (p = 0.001) were found to be significantly low in BC patients, no statistically substantial difference in the BMD levels of BC patients suffering from metastasis was observed. It was observed that urine alpha-CTx (specificity: 70%; sensitivity: 85%) values are critical factors that differentiate BC patients with metastasis from BC patients without metastasis. Conclusions: We found that alterations in bone turnover could be detected by using the values of urine alpha-CTx while differentiating BC patients with metastasis from BC patients without metastasis. Using the biochemical markers of bone turnover and BMD together would be pertinent for determining the level of metastasis present and examining the efficiency of bone density preservation therapy. Ideally, BMD measurement would be evaluated together with biochemical markers.
Keywords: breast cancer; bone mineral density; bone turnover markers; N-terminal cross-linking telopeptide; C-terminal cross-linking telopeptide of type I collagen; DIAGNOSTIC-VALUE; RESORPTION; CROSSLAPS; PATTERN; CTX; General & Internal Medicine